Literature review: relationship between anemia and abortion in pregnancy - Dewi (International Journal of Nursing and Midwifery Research, 2023)
WHO data shows the number of the population experiencing anemia worldwide is 83.2% from 114 countries, while in Southeast Asia it reaches 97.8%. The incidence of anemia in pregnant women in Indonesia ranks fourth together with Thailand, which is 30%. This figure is higher than Malaysia and Singapore, namely 27% and 28%. WHO reports that there are 52% of pregnant women experiencing anemia in developing countries. The prevalence of anemia in pregnant women in Indonesia is 70%, or 7 out of 10 pregnant women suffer from anemia. To review some of the literature on the relationship between anemia and abortion in pregnancy. The research design uses Literature Review or literature review by collecting data from the topic of anemia and the incidence of abortion in pregnancy. Data sourced from searches using the word abortion, anemia and pregnancy through databased Scient direct, PubMed and books. Eight articles stated that there was a significant relationship between anemia and abortion. One article showed different research results, namely that there was no significant relationship between anemia and abortion. Anemia can be one of the causes of abortion in pregnancy, but abortion is not always caused by anemia during pregnancy.